The Behavior and Load-Carrying Capacity of Unstiffened Seated Beam Connections - Chen, Wai-Fah; Bowman, Mark D.; Yang, W.H. (Engineering Journal, 1997)
Unstiffened seated-beam connections are often used to connect a beam to a column. For many years this connection was designed by using tabular methods in the AISC Design Manuals, including the most recent LRFD Manual. The manual tables are generated based on the required bearing length method developed in 1940s. This paper investigates the validity of this method by examining the formulations of the model and analyzing the connection behavior. The interactions between connection components are discussed and more rational and accurate models are developed for connections consisting of a flexible angle and a stiff beam. Through comparison of various results, the current LRFD procedures are assessed and practical implications of this research are summarized.